IMPLEMENTATION OF MARRIAGE FREEDOM FOR CHILDREN NOT AGE ENOUGH, BASED ON THE DECISION OF THE PRINGSEWU REGIONAL COURT (Study Decision Number: 10/Pdt.P/2023 /PA.PRW) - Baharudin, Baharudin; Anggaalfian, Anggaalfian; Kristinasafitri, Kristinasafitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2024)
Premeditated murder is a murder committed with time planning with the aim of ensuring the success of the murder or avoiding the arrest of the perpetrator F, which causes the crime of premeditated murder to occur simultaneously with attempted suicide, based on Decision No. 102/ Pid. .B/2022/PN. Cla. The accused killed the victim because he was jealous of seeing the victim walking with another man, so the accused intended to kill the victim a week before December 18, 2021. The application of criminal law against perpetrators of the crime of premeditated murder with attempted suicide based on Decision No. 102/Pid.B/2022/PN.Kla, namely the defendant Sosiadi Fariyon acted as Ion Bin Karnadi who was proven to violate the provisions of Article 340. According to the Criminal Code, the defendant was threatened with a prison sentence of 20 (twenty years. premeditated murder based on attempted suicide made by the judge in Order Number 102/Pid.B/2022/PN.Kla. The first thing is that the prosecutor can prove it. allegations, there is no reason or justification, the fulfillment of 2 (two) pieces of evidence and the conditions complicating the defendant's actions, disturbing the community and facilitating the defendant, polite and remorseful for his actions and the defendant was never punished.